(3fSje GdnqUHG hfOje GdpqUHGs - (3GdQhej Gdecj GdegJGQj, GdegJGQ, EHQGgje Hf jhSa, J (B1071(3g`s
(3ChdgG (B:s
((3CUfGa GdNhGQL(B) (3HSe Gddg Qhj Yf QShd Gddg Udi Gddg Ydjg hSde Cfg bGd Ef Hfj ESQGFjd GaJQbhG Ydi GKfJjf hSHYjf aQbI hEf GeJj JaJQb Ydi KdGK hSHYjf aQbI cdge aj GdfGQ EdG GdShGO GdCYXe s
(3BNQgG (B:s
(3ehGYX fGaYI hef ahGFO GdTjN GHf QSdGf bGd de CRd CSeY aj CdSfI GdfGS GdOYGA HNGJeI GdNjQ hde CLO dPdc CUdG MJi XaQJ HPdc aj GdMdjI ef WQjb GdUdJ Hf YGUe GdeQGOj Jes
(3JHUQI GdeDda (B:s
(3GdegJGQ LGAJ cdbH aj GdCYdGe haj fSNI fSje GdUHG GdeNWhWI (B, (3hcfSHI LGAJ aj eYLe GdeDdajf hgOjI GdYGQajfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\82s
(3gOjI GdYGQajf (B1\33s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs